Essays on financial stability and climate risk - Fülber, Ives Cézar (2024)
This thesis is composed of three essays concerning financial stability and climate risk. The first chapter is a comparative bibliometric study analyzing trends in the literature regarding Financial Stability and its counterpart, Financial Instability. We have clustered the keywords in the articles being analyzed and used dummy variables indicating the presence of these clusters as independent variables in regression models predicting total and yearly citations in order to determine relevant themes on the literature. Our findings suggest that both approaches focus on avoiding the negative effects of instability by ensuring financial stability. Among the concerns with external shocks, the impact of climate risk is emerging as a growing theme in both literatures. Given the global concern about energy, food security and climate change, the second and third chapters examine the interconnectedness of markets relevant to these themes. In the second chapter we investigate the spillover effects amidst the EU ETS, Energy and Agrifood markets. Applying the novel R2 decomposed connectedness approach we find that the impact of the contemporaneous spillover in the total connectedness is significant, while the lagged effects contribute substantially when looking at the net spillover. Corn appears as the main net transmitter and Carbon is mostly a net receiver. The Russian-Ukraine war affected the markets, given Ukraine’s role in food production and the impact of the conflict on Europe’s access to Natural Gas, increasing Coal use. Lastly, the third chapter is focused on the China National Emission Trading System (ETS), which has the potential to play a major role in reducing the country’s carbon emissions. We investigate the interconnectedness between the China ETS market and assets from the Energy and Agrifood sectors along with two metal commodities with special relevance to China and energy transition efforts. Corn and Natural Gas appear as the main net transmitters and China ETS and Wheat as the main net receivers.